2007
DOI: 10.12968/bjon.2007.16.13.24243
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the value of silicone and hydrocolloid products in stoma care

Abstract: Intact skin among many other functions provides a protective barrier between the body and its environment, which is critical in regulating transepidermal water loss (Wilkinson and Moor, 1982). The frequent application and removal of adhesives can damage skin by stripping away the outer epidermal layers. Older people, very young children and those with an underlying skin disorder may be particularly at risk (Gibelli et al, 1999; Lyons and Smith, 2003). Hydrocolloid adhesives, which hold moisture in the adhesive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Some characteristics of alcohol-and silicone-based adhesive removers are summarised in Table 13 (page S19). 34,35 e anatomical location where the adhesive remover will be applied should in uence selection-for example, avoid sprays above the neck and use liquid sachets with caution where there is a risk that the contents might enter the body.…”
Section: Adhesive Removersmentioning
confidence: 99%
“…Some characteristics of alcohol-and silicone-based adhesive removers are summarised in Table 13 (page S19). 34,35 e anatomical location where the adhesive remover will be applied should in uence selection-for example, avoid sprays above the neck and use liquid sachets with caution where there is a risk that the contents might enter the body.…”
Section: Adhesive Removersmentioning
confidence: 99%
“…There are approximately 650 stoma specialist nurses in the UK. 7 There are several documents to guide the stoma care provided in the UK. Three of these were written in the past few years, two that were published on behalf of the Royal College of Nursing and one by the World Council of Enterostomal Therapists UK.…”
Section: Uk Stoma Care Guidancementioning
confidence: 99%
“…Adhesives spread over the skin surface into crevices and surface detail. The effectiveness of the adhesive is dependent on the adhesive chemistry, the risk of irritation from the adhesive, allergic reaction to the materials, minor inclusions in the adhesive system, which can cause contact dermatitis, and the restriction of transpiration of moisture by the adhesive product (Berry et al, 2007). The removal of adhesive products will remove loosely bound epidermal cells and, with repeated use of adhesive products, can strip away varying amounts of the stratum corneum (superficial epidermis) layer (Dykes et al, 2001;Zillmer et al, 2006).…”
Section: Skin Stripping and Integritymentioning
confidence: 99%
“…As Lyon and Smith (2010) note, patients who physically pull their stoma appliance off to remove it, rather than easing it from the skin, are more likely to suffer from peristomal skin breakdown. Berry et al (2007) observe that appliance removal will inevitably lead to the removal of loosely bound epidermal cell layers and that more cells will be removed as the process continues. Williams et al (2010), in an 80-ostomate study, reported that 68% of patients had peristomal skin problems with repeated application and removal of stoma appliances, which affected peristomal skin.…”
Section: Peristomal Skinmentioning
confidence: 99%